Remove silver ions from aqueous solutions Using the Bentonite (Latakia University Journal -Basic Sciences Series, 2019)
In this work, the possibility of using natural bentonite was studied in the process of removing silver ions from their water solutions. The X-Ray was analyzed by X-ray analysis and functional groups using FT.IR technique. The sample surface area of ​​the sample was determined by absorbing and adsorbing nitrogen at 77k using the BET method.The results showed that the optimal time to reach the equilibrium state was 20 minutes. The removal rate was 92%. Several granular sizes were tested for the bentonite. The best granular size was 250µm. The silver removal ratio was 87%. Different pH values ​​were tested. Removal ratio is highest at pH = 6.Depending on the conditions used in this research, the method is practical and economically and environmentally appropriate because it helps to reduce the pollution resulting from the presence of silver ions